Clash of the Titans: Does Internet use Reduce Television Viewing? - Liebowitz, Stan J.; Zentner, Alejandro (The Review of Economics and Statistics, 2012)
We examine the impact of the Internet on the leading American recreation activity: watching television. We run a panel regression using television viewing, Internet penetration, and socioeconomic variables for a large number of American cities starting before the birth of the Web. We find that the Internet's effect on television viewing varies by age group, reducing it by a moderate amount for the youngest Americans but having no impact on the viewing of the oldest Americans. We hypothesize that the overall effect is likely to increase over time as older age groups have more experience with the Internet's recreational opportunities.